MENINGKATKAN HASIL BELAJAR SISWA SD PADA MATERI HUBUNGAN SUMBER DAYA ALAM DENGAN LINGKUNGAN MELALUI PENERAPAN MODEL KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIVEMENT DIVISION) - Isnawati Isnawati (Universitas Lambung Mangkurat, 2011)
Has done research on the application of the model STAD on the material of natural resources and environment in the fourth grade student of SDN 9 Tanjung. Classroom action research is intended to increase student's understanding of the relationship of natural resources and the environment and increase positive attitudes fourth grade students of SDN 9 Tanjung to the environment. This study uses a classroom action research model of Kemmis and Taggart spiral from one to the next cycle. Each cycle includes (1) planning, (2) action, (3) observation, and (4) reflections. The results showed that: (1) model with cooperative learning type STAD can improve student learning outcomes in the matter of natural resources and environment marked by increasing exhaustiveness student learning by 50%. (2) The application of cooperative model type STAD can improve students' positive attitudes to the environment. Key word : cooperative model, STAD, natural resources and environment